CPT1A-Mediated Fatty Acid Oxidation Promotes Precursor Osteoclast Fusion in Rheumatoid Arthritis - Huang, Zhaoyang; Luo, Rong; Yang, Liu; Chen, Haiqi; Zhang, Xinyao; Han, Jiawen; Wang, Hongxia; Zhou, Zhongyang; Wang, Zhao; Shao, Lan (Frontiers in Immunology, 2022)
The overproduction of osteoclasts, leading to bone destruction in patients with rheumatoid arthritis (RA), is well established. However, little is known about the metabolic dysfunction of osteoclast precursors (OCPs) in RA. Herein, we show that increasing fatty acid oxidation (FAO) induces OCP fusion. Carnitine palmitoyltransferase IA (CPT1A), which is important for carnitine transportation and is involved in FAO in the mitochondria, is upregulated in RA patients. This metabolic change further increases the expression of clathrin heavy chain (CLTC) and clathrin light chain A (CLTA) by enhancing the binding of the transcription factor CCAAT/enhancer binding protein β (C/EBPβ) to the promoters of CLTA and CLTC. This drives clathrin-dependent endocytosis pathway, which attenuates fusion receptors in the cellular membrane and contributes to increased podosome structure formation. This study reveals a new mechanism through which FAO metabolism participates in joint destruction in RA and provides a novel therapeutic direction for the development of drugs against bone destruction in patients with RA.